CA 27-29: A Valuable Marker for Breast Cancer Management in Correlation with CA 15-3 - Hiba Sarmad Kamal AL-Azzawi1 , Manal Kamal Rasheed2 , Manwar AL-Naqqash3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Breast cancer is the most common invasive cancer in women, and second main cause ofcancer death in women after lung cancer. Tumor markers that showed evidence of clinical utility and wererecommended for use in practice include CA15-3, CA27-29 and Carcinoembryonic.Aim of the study: This study was designated to measure the levels of CA15-3, CA27-29 and CEA andevaluate their clinical significance in metastasis and non- metastasis patients with breast carcinoma,comparing their sensitivity and specificity.Patients, Materials and Methods: Serum levels of (CA27-29) and (CA15-3) were measured in 62 patients(40 in non-metastasis and 22 in metastasis patients). The age of patients was from (30 to 90) years old.Samples were collected from the Oncology Teaching Hospital in Baghdad Medical City.Results: The levels of CA15-3, CEA were significantly higher in metastasis group compare to non-metastasisgroup. while the levels of CA27-29 were no statically significant difference between the two groups.Conclusion: In this study, measurement of CA15-3 and CEA correlated with disease activity especiallyin the metastatic setting. on the contrary, CA27-29 did not show such clear correlation. CA15-3 was moresensitive in follow up of breast cancer patients followed by CEA and then CA27-29.